KONSEP PENDIDIKAN KARAKTER DI SEKOLAH - Medi Romi Ardianto (LPPM Institut Al-Ma`arif Way Kanan Lampung, 2020)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that students can actively develop their potential. Character education is a plus character education, which involves aspects of cognitive, feeling, and action. In the Islamic perspective character education consists of seven important things namel; Robbaniyah, Insaniyah, Syumuliyah, Al-Waqi’iyyah, Al-Wasathiyah, Al-Wudhuh, dan Al-Jam’u Baina Ats Tsabat wa Al Murunnah. Which of the seven is not found in other religions and this is also one of the reasons why so many people are attracted to Islam so that they claim to convert to Islam. This is also the reason why Islam is the only religion that is not